Building trust in luxury brands through behavioral analytics of customer experience - Cherep, Nataliia (Актуальні питання економічних наук, 2025)
In today’s increasingly competitive luxury brand market, the issue of trust as a key intangible asset that determines the strength and duration of the relationship between the brand and the consumer is particularly relevant. The formation of trust in a luxury brand is associated not only with the quality of the product, but primarily with the integrity of the customer experience, which combines emotional, symbolic and service components of interaction. That is why the study of behavioral analytics mechanisms is becoming an essential prerequisite for sound management of the reputational capital of luxury brands. The purpose of the article is to theoretically substantiate and conceptually highlight the mechanisms underlying trust formation in luxury brands through behavioral analytics of customer experience. The article analyzes modern approaches to interpreting consumer behavior models and identifies structural elements of customer experience that play a key role in strengthening brand trust. The research methods include a systematic and comparative analysis of scientific sources, content analysis of analytical tools for studying consumer behavior, generalization of empirical observations of client practices, and logical-structural modeling of relationships between various factors. The research results reveal the multilevel nature of trust, which is shaped by the integration of data on digital activity, offline interactions, emotional reactions, and the stability of service standards. The structure of the behavioral drivers of trust in luxury brands is established, including emotional, perceptual, and service factors of interaction. The mechanisms of trust formation are identified, which are manifested through service stability, symbolic rituals, personalization, and consistent brand communication. A conceptual model of behavioral analytics is formed, which describes the transition from collecting behavioral data to making management decisions. The causal relationships between analytical observations of customer experience and corresponding strategic actions aimed at strengthening trust are outlined. The conclusions emphasize that the use of behavioral analytics provides a more accurate interpretation of consumer motives and contributes to the formation of sustainable mechanisms of personalization and service compliance – key determinants of trust. The need for further development of analytical tools to predict long-term loyalty patterns in the luxury brand field is emphasized.